Carbon dioxide poisoning: a literature review of an often forgotten cause of intoxication in the emergency department - Permentier, Kris (Int J Emerg Med, 2017)
The goal of this article was to provide an overview of the literature available on carbon dioxide intoxication. Articles were included based on their focus on medical or physiological effects of carbon dioxide. Studies related to decompression sickness were excluded. Mechanisms of carbon dioxide poising (both as an asphyxiant and as a toxicant) were described. Our review suggested that precautions are needed when handling dry ice or while working in confined spaces. Pre-hospital responders also need to pay attention for the possible diagnosis of CO(2) intoxication for their own safety. When confronted with a victim, he/she should be removed from the dangerous area as fast as possible and oxygen should be administered. Without adequate treatment, victims may show acute reduced cognitive performance, respiratory failure, and circulatory arrest. Therefore, carbon dioxide poisoning is a rare but not to miss diagnosis in the emergency department.